Methods of using cloud services in foreign language training - Hennadiy M. Kravtsov; Olga O. Gnedkova (Academy of Cognitive and Natural Sciences, 2018)
Research goals: determine particularities of using cloud services in English communicative competence forming process and develop the model of distance learning system (DLS) and cloud services interaction that improves the quality of the learning process. Research objectives: to identify, describe and develop methodological features of the model of distance learning system and cloud services interaction; consider on the examples the methods of use cloud services in DLS in foreign language training, aimed at English communicative competence forming process of students; experimentally investigate the level of using of cloud services in distance learning and identify ways of improving its use. Object of research: methodical system of foreign language students' training of language faculties in high institutions. Subject of research: methodological model of the model of distance learning system and cloud services interaction in English communicative competence forming process. Research methods used: review and analysis of scientific publications, psychological, educational and instructional materials, modeling of complex systems, questionnaires, conducting pedagogical experiment. Results of the research. The model of distance learning system and cloud services interaction was developed and the methodological particularities of this interaction are defined. Methods of using cloud services on the example of the distance course "Practical English Course Upper Intermediate" describing the methods of doing the tasks in English communicative competence forming process of language faculties were considered. As a result of experiment it was found there is a low level of use of cloud technologies in distance learning is a consequence of a lack of awareness of teachers in the possibilities of its use. The main conclusions and recommendations: 1) the use of cloud technologies in distance learning of foreign language will improve the quality of training of students of language faculties of high institutions; 2) it is reasonable to conduct work in familiarization and training university lecturers using cloud services in professional and educational activities.